Left ventricular myocardial remodeling in playing sports athletes - E. V. Bryntseva (National Electronic Information Consortium (NEICON), 2022)
The article presents the results of an echocardiographic study of 64 male playing sports athletes (basketball and football). The results of the study showed that up to the age of 19 in playing sports athletes, only normal geometry of the left ventricle is observed. With age and, accordingly, with an increase in the experience of playing sports, the number of eccentric and concentric remodeling and eccentric and concentric myocardial hypertrophy increases statistically. The percentage of concentric myocardial hypertrophy (pathological remodeling) was 6.5 %, 12.5 % and 7.7 % in the groups 19-25 years old, 26-30 years old and 31 and older, respectively, which must be taken into account when taking measures to prevent overtraining and sudden cardiac death in sports.